The deception in the identity of the fish bought in some of the biggest cities of Argentina - Delpiani, G.; Deli Antoni, M. Y.; Covatti, M.; Fischer, L.; Díaz de Astarloa, J. M.; Olivera, C. [UNESP]; Delpiani, S. M. (Elsevier, 2024)
Falsification and mislabeling practices represent the most frequently highlighted fraud incidents affecting customer trust, human health, supply chain economies, and stock preservation. The main objective of this work was to estimate the levels of mislabeling or replacement of fresh fish fillets in six of the most populous cities in Argentina (Bahía Blanca, Buenos Aires - and in particular the neighborhoods Chinatown, La Plata, Mar del Plata, Córdoba, and Rosario). DNA barcoding revealed a total mislabeling rate of 36.65% (70 cases), with most incidents occurring with Thunnus albacares (21), and Callorhinchus callorynchus (22) which were mostly misnamed. The city with the highest mislabeling incidence was Mar del Plata (55%), while no cases were recorded in Chinatown, a neighborhood in Buenos Aires. Almost 70% of the replacements/mislabeling involved Chondrichthyes, mainly C. callorynchus and Mustelus schmitii. All chondrichthyans used for replacements are classified as critically endangered, near threatened, and vulnerable by the IUCN, highlighting the prevalence of misidentification and replacement in this extremely vulnerable group. It is essential to emphasize that mislabeling contributes to illegal, unreported, and unregulated fishing, a critical issue for the future sustainability of fish. Argentina lacks legislation on traceability and labeling, underscoring the need to improve accuracy and transparency in the labeling and identification of fish and seafood products throughout the country.
Keywords: COI; Conservation; DNA barcodes; Food traceability; Fraud